Procedure for optimization calculation of structures of suspended electromagnetic separators - G. A. Koschuk; K. I. Nikitin; A. S. Tatevosyan; N. A. Tereshchenko (Омский научный вестник)
The article is devoted to the technique for optimizing the structures of suspended electromagnetic separators based on the minimum weight of active materials used for their manufacture. Optimization procedure is based on output of equations of relationship of design parameters of electromagnetic separators to specified criteria. During development of the optimization technique there is used the assumption of the plane-parallel nature of the magnetic field under the pole tips of the electromagnetic separator, thanks to which the formula for magnetic force at the middle of the interpole gap is derived. The effect on the maximum magnetic force of the length of the pole tips, the inter-pole gap and the height of the suspension of the electromagnetic separator has been investigated. Based on the developed optimization methodology, an algorithm for calculating optimal structures of suspended electromagnetic separators has constructed.